1993
DOI: 10.1159/000107339
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Secretion in Alzheimer's Disease: Studies with Growth Hormone-Releasing Hormone Alone and Combined with Pyridostigmine or Arginine

Abstract: There is evidence that GH secretion is reduced in normal elderly subjects as well as in patients with Alzheimer''s disease (AD). To clarify the mechanisms underlying this GH hyposecretory state in 14 elderly subjects (age 65–75 years) and 15 AD patients (age 61–78 years), we studied the effects of both pyridostigmine (PD, 120 mg orally), a cholinesterase inhibitor, and arginine (ARG, 0.5 g/kg i.v.), two substances likely acting via inhibition of hypothalamic somatostatin, on GH response to GHRH (1 (µg/kg i.v.)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 23 publications
4
18
0
Order By: Relevance
“…Indeed, cholinergic agonists are able to increase both spontaneous and GHRH-induced GH secretion in AD patients [142,[152][153][154]156] without any difference with normal elderly [142,153], although both responses are reduced compared with normal young subjects [142]. These findings, therefore, confirmed the presence of neuroendocrine cholinergic derangement in the ageing brain but demonstrated that, at least at hypothalamic level, cholinergic pathways are not more impaired in AD than in normal elderly.…”
Section: Igf-imentioning
confidence: 54%
See 4 more Smart Citations
“…Indeed, cholinergic agonists are able to increase both spontaneous and GHRH-induced GH secretion in AD patients [142,[152][153][154]156] without any difference with normal elderly [142,153], although both responses are reduced compared with normal young subjects [142]. These findings, therefore, confirmed the presence of neuroendocrine cholinergic derangement in the ageing brain but demonstrated that, at least at hypothalamic level, cholinergic pathways are not more impaired in AD than in normal elderly.…”
Section: Igf-imentioning
confidence: 54%
“…On the other hand, other studies focusing on the effects of other neuroactive drugs able to stimulate GH secretion, such as clonidine, pyridostigmine and apomorphine, generally confirmed that AD shows a GH response similar to that in normal elderly subjects [141,142,[152][153][154][155][156].…”
Section: Igf-imentioning
confidence: 77%
See 3 more Smart Citations